Contribution of the renin-angiotensin system to subsensitivity of soluble guanylyl cyclase in TGR(mREN2)27 rats - Jacke, Kerstin; Witte, Klaus; Huser, Lutz; Behrends, Sönke; Lemmer, Björn (European journal of pharmacology, 2000)
Soluble guanylyl cyclase activity and its stimulation by diethylamineNONOate was measured in aortae from hypertensive TGR(mREN2)27 rats (TGR) and Sprague-Dawley controls. Superoxide dismutase was added in vitro to evaluate the contribution of oxidative breakdown of nitric oxide (NO) by superoxide anions. Expression of soluble guanylyl cyclase was assessed by reverse transcriptase-polymerase chain reaction (RT-PCR). Basal and stimulated soluble guanylyl cyclase activity was significantly reduced in TGR rats, addition of superoxide dismutase had no effect. Expression of soluble guanylyl cyclase subunits was not different between strains. The independent contribution of hypertension and the overactive renin-angiotensin system to soluble guanylyl cyclase subsensitivity was assessed after normalization of TGR's blood pressure by the Ca2+-channel blocker amlodipine or the angiotensin converting enzyme-inhibitor enalapril. Soluble guanylyl cyclase activity in TGR was slightly increased by amlodipine and almost completely restored by enalapril. In conclusion, TGR showed desensitized vascular soluble guanylyl cyclase, depending on their overactive renin-angiotensin system.
Gesehen am 14.04.2022